UGT709G1 a novel uridine diphosphate glycosyltransferase involved in the biosynthesis of picrocrocin, the precursor of safranal in saffron (Crocus sativus) - Diretto, Gianfranco (The New phytologist, 2019)
© 2019 The Authors. New Phytologist © 2019 New Phytologist Trust.